2001
DOI: 10.1128/iai.69.9.5619-5625.2001
|View full text |Cite
|
Sign up to set email alerts
|

Absence of All Components of the Flagellar Export and Synthesis Machinery Differentially Alters Virulence ofSalmonella entericaSerovar Typhimurium in Models of Typhoid Fever, Survival in Macrophages, Tissue Culture Invasiveness, and Calf Enterocolitis

Abstract: In this study, we constructed an flhD (the master flagellar regulator gene) mutant of Salmonella enterica serovar Typhimurium and compared the virulence of the strain to that of the wild-type strain in a series of assays that included the mouse model of typhoid fever, the mouse macrophage survival assay, an intestinal epithelial cell adherence and invasion assay, and the calf model of enterocolitis. We found that the flhD mutant was more virulent than its parent in the mouse and displayed slightly faster net g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
167
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(182 citation statements)
references
References 39 publications
11
167
2
2
Order By: Relevance
“…The ability to move through the use of these extracellular flagella has been shown to be essential for the pathogenesis of other bacteria, including Proteus mirabilis (Burall et al, 2004;Mobley et al, 1996), Salmonella species (Schmitt et al, 2001), Helicobacter pylori (Terry et al, 2005), and even enteropathogenic E. coli (Giron et al, 2002). Recently, several studies have indicated that there is a role for motility and the presence of flagella in UPEC pathogenesis (Lane et al, 2005;Wright et al, 2005;Haugen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to move through the use of these extracellular flagella has been shown to be essential for the pathogenesis of other bacteria, including Proteus mirabilis (Burall et al, 2004;Mobley et al, 1996), Salmonella species (Schmitt et al, 2001), Helicobacter pylori (Terry et al, 2005), and even enteropathogenic E. coli (Giron et al, 2002). Recently, several studies have indicated that there is a role for motility and the presence of flagella in UPEC pathogenesis (Lane et al, 2005;Wright et al, 2005;Haugen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial flagellin is a virulence factor of S. enterica. Strains of Salmonella deficient in flagellin can exhibit defects in colonization and tissue invasion, as well as invasion of macrophages and epithelial cells in vitro [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting data have suggested that motility has a negligible role in the bacterial attachment compared to bacterial density (7,8). Furthermore, a nonflagellated mutant strain of Salmonella enterica serovar Typhimurium was able to attach to cultured intestinal epithelial cells but was impaired in its ability to invade the cells (9). Similarly, a nonflagellated mutant of S. Enteritidis was 50-fold less invasive to Caco-2 cell lines, even if the adhesion rate was similar to that of a flagellated strain (10).…”
mentioning
confidence: 88%
“…Motility. Motility was determined by stabbing motility agar with a bacterial strain and assessing migration from the stab after incubation at 37°C for 18 h. Motility agar consisted of 10 g of tryptone and 5 g of NaCl per liter plus 0.35% (wt/vol) agar (pH 7.4) (9).…”
Section: Methodsmentioning
confidence: 99%